Adopción del uso del filtro de agua en la mejora de la salud en la comunidad de Aucayo. Loreto, 2024 - Calixtro Agüero, David Alexander (2024)
Access to potable water in the community of Aucayo, Loreto, has been a challenge, contributing to a high incidence of diseases. This study evaluated the impact of adopting a water filtration system on the health of its inhabitants. Through surveys conducted with 43 users, it was found that 95.35% showed a high level of acceptance of the system, with a significant decrease in diseases related to contaminated water and improvements in the quality of life of the residents. Although the system was well received, areas for improvement in training and maintenance were identified. In conclusion, the water filtration system has improved the quality of life in Aucayo, and it is recommended to strengthen technical support to ensure the project's sustainability.